Effects of plant population on soybean - Rosolem, C. A.; Silvério, J. C. O.; Nakagawa, J. (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were led to study the effects of plant population, fertilizer level and planting time upon soybean (Glycine max (L.) Merrill, cv. UFV-1) yields and yield components. In the first experiment the soybean was grown on a Dark-Red Latosol (clay), fertilized with 100, 200, 300 and 400 kg/ha of the 0-33-12 formula, utilizing the populations of 10, 20, 30 and 40 plants per meter of row. In the second experiment, carried out on a "Latosol Roxo" (clay), soybean was planted in November and December, with populations of 8, 16, 24, 32 and 40 plants per meter of row. The results showed that the increase in plant population caused a lower production per plant, as function of the lower pod number per plant. The fertilization levels did not influence the grain production significantly or the yield components.